Effects of Imidacloprid in the Development of Non-Alcoholic Fatty Liver Disease and the Effects of Exercise Training - Jolin-Rodrigue, Gabriel (Université d'Ottawa / University of Ottawa, 2019)
The non-alcoholic fatty liver disease (NAFLD) is the most common liver pathology in developed countries with an estimated prevalence of 20 to 30% in the American population. A typically benign and asymptomatic pathology, NAFLD is characterized by hepatic steatosis and abnormal levels of hepatic enzymes stemming from an increase in circulating free fatty acids originating from white adipose tissue lipolysis, an increased de novo lipogenesis, reduced fatty acid oxidation and decreased hepatic triglycerides secretion, all within an insulin resistance context. NAFLD has the potential to progress to the non-alcoholic steatohepatitis (NASH), a condition marked by inflammation, advanced oxidative stress and fibrosis. NASH is expected to be the leading cause of liver transplant by 2020 due to its complications (i.e.: cirrhosis, hepatocellular carcinoma and liver failure). Various xenobiotics such as pesticides have been shown to promote the apparition and development of NAFLD. Of interest to this study is the neonicotinoid imidacloprid, more contemporarily known for its suspected role in the colony collapse disorder of various anthophilae species. Imidacloprid has been shown to induce hepatic oxidative stress in rats, a significant factor in the development of NAFLD and its progression to NASH. Lifestyle modifications, namely physical exercise, is a current treatment which has been proven beneficial to prevent and treat NAFLD by reducing hepatic steatosis, oxidative stress and improving insulin sensitivity. The role of any neonicotinoid on the development of NAFLD has yet to be examine and few have looked at the role of exercise in the treatment of NAFLD brought about by pesticide contamination.
Keywords: Neonicotinoid; Imidacloprid; Non-alcoholic fatty liver disease; NAFLD; Exercise; Liver; Sprague-Dawley; Xenobiotics